Unveiling the Power of Emotional Intelligence: A Dynamic Exploration of Its Impact on Proactive Decision-Making - Demissie, Esayas Degago; Molnár, Edina (Emerging Science Journal, 2025)
In this multifaceted, dynamic business world, leadership success and effective decision-making are highly dependent on understanding and controlling emotional intelligence (EI). In this multifaceted world of work, the integration and strategic use of emotional intelligence (EI) drives change and facilitates proactive and effective decision-making. The study aims to examine the direction and degree of relationship that exists between EI and proactive decision-making using one of the public service institutions in Ethiopia, the Ethiopian Customs Authority. The study uses a quantitative and correlational design utilizing a structured survey administered to a randomly selected sample of 156 employees. The study applied statistical analysis techniques, including correlation and stepwise regression analysis, to determine the strength and significance of the relationship between EI and proactive decision-making. Research has examined how and in what direction EI competencies (emotion perception, regulation, and utilization) influence features of proactive decision-making. The result accentuates that Emotional intelligence emerges as a critical driver, accounting for a substantial proportion of the observed differences in individuals' ability to make proactive decisions. Grounding on the findings, the study highlights the necessity of integrating EI training programs into organizational development strategies to enhance employees' decision-making capabilities, adaptability, and resilience in dynamic workplace environments.